Musculoskeletal Disorders Especially Sprain their Various Effects and Possible Effective Therapies in Modern Age - Fatima, Maham; Arslan, Muhammad; Akhtar, Mehnaz; Kabeer, Fahad; Nasreen, Khalida; Rafique, Maheen; Iqbal, Mudassar (Indus Journal of Bioscience Research, 2025)
Musculoskeletal disorders (MSDs) are characterized by damage to the locomotive system, including muscles, bones, ligaments, joints, tendons and nerves often caused by extrinsic factors including trauma, psychosocial factors and high biomechanical exposure. These disorders mostly affect individuals’ routine work and productivity, leading to absenteeism and early retirement, as treatments are costly, leading to prolonged individual suffering. The occupational group that is particularly affected by this disorder is teachers; here its prevalence is higher than in other professions due to the tough routine, physical load and demands of their work. Sprains, particularly ankle sprains, are one of the most common musculoskeletal injuries around the world, especially in athletes and physically active persons. In terms of sports-related trauma, ankle injuries rank next to knee injuries. Male and female athletes exhibit distinctive patterns in the incidence of ankle sprains. These disorder leads to severe socioeconomic loss especially in developing countries. This review provides an overview of the diagnosis of MSDs, including MRI and sonography, the most efficient methods of diagnosis. The effective treatment includes cryotherapy, drug-based treatment, and the PRICE protocol which have been discussed along with advanced treatment methodology including PRP and shockwave therapy.